Compositional dependence of the optical properties of novel Ga–Sb–S–XI (XI = PbI2, CsI, AgI) infrared chalcogenide glasses. Issue 2 (6th October 2017) - Huang, Xinyu; Jiao, Qing; Lin, Changgui; Xu, Tiefeng; Ma, Hongli; Zhang, Xianghua; Dai, Shixun
Abstract: A novel family of Ga2 S3 –Sb2 S3 –XI (XI = PbI2, CsI, AgI) was investigated to understand the role of metal halides and exploit new chalco‐halide glasses for infrared optics. The dependence of the thermal properties, infrared optical properties, and structural information of the novel family on different metal–iodines was investigated. Results showed that metal halides increase the glass stability but decrease the glass network connectivity. The compositional dependence of the short‐wave cut‐off edge is associated with the electronegativity difference between the cations and anions of the metal halides. Raman study showed that the metal–iodine modified the glass structure mainly through the iodide content, and the cations dissolved in the glass network mostly as charge compensators for the aperiodic network. For the glasses in the series Ga2 S3 –Sb2 S3 –XI–Dy 3+, Dy 3+ emission increased in the PbI2 ‐ and CsI‐doped glasses but decreased in the AgI‐doped glass due to the combined effect of dysprosium and oxygen. For all that, these novel glasses are highly promised for use in infrared optics.